Arah baru pendidikan Islam di Indonesia - Rahim, Husni, 1946- (Ciputat, Indonesia : Logos Wacana Ilmu, 2001)
History and concepts of Islamic education in Indonesia
Daftar kepustakaan : p. [229]
Keywords: Islamic education -- Indonesia